THE IMPACT OF RENEWABLE ENERGY DEVELOPMENT ON EMPLOYMENT IN ARABIAN GULF COUNTRIES (World Economics and Finance Bulletin, 2023)
Given the considerable potential of renewable energies, the transition towards their utilization is poised to provide a substantial influx of employment opportunities across several industries. Moreover, this shift is expected to serve as a fundamental catalyst for fostering sustainable development. Based on the reports published by the World Renewable Energy Organization, it is anticipated that the utilization of renewable energy resources within individual regions will significantly contribute to the overall augmentation of employment prospects across various sectors, encompassing production equipment, construction, administration, and services. Given the significance of this matter, the present study used the dynamic ordinary least squares (DOLS) approach for estimate purposes. In this study, we apply the Pooled Mean Group (PMG) approach proposed by pesaran et al. (1999) to examine the influence of renewable energy technology development on the employment rate in the Arabian gulf countries from 2010 to 2021 . The empirical findings suggest that the implementation of renewable energy initiatives in the Arabian gulf nations will have favorable outcomes in terms of employment, leading to a notable rise in job opportunities within these respective regions .
Keywords: Renewable energy; employment; developing countries; developed countries